1998
DOI: 10.1093/jn/128.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I and II Receptor Expression in Rat Colon Mucosa Are Affected by Dietary Lipid Intake

Abstract: Epidemiologic data and animal models have demonstrated a correlation between dietary fat composition and colon cancer risk. We have previously found that dietary fat alters cell proliferation in rat colon, which may influence the risk of colon cancer. Growth factors, including insulin-like growth factor (IGF) I and II, regulate the cell cycle in most mammalian tissues. Hence, we measured IGF-I and IGF-II receptor expression in colonocytes from Sprague-Dawley rats fed diets containing either beef tallow (BT) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…It has been postulated that insulin has a mitogenic effect by multiple and complex mechanisms. First, insulin might bind and activate its related insulin‐like growth factor‐1 receptor, which is the most frequently proposed mechanism to explain the clearly increased risk of cancer in diabetic patients 1–11 . Second, hyperinsulinemia might increase the risk of certain cancers by increased insulin receptor signaling, leading to proliferative and anti‐apoptotic effects 72 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that insulin has a mitogenic effect by multiple and complex mechanisms. First, insulin might bind and activate its related insulin‐like growth factor‐1 receptor, which is the most frequently proposed mechanism to explain the clearly increased risk of cancer in diabetic patients 1–11 . Second, hyperinsulinemia might increase the risk of certain cancers by increased insulin receptor signaling, leading to proliferative and anti‐apoptotic effects 72 .…”
Section: Discussionmentioning
confidence: 99%
“…An animal study showed that colonocytic IGF-I receptor expression increased with an increased dietary lipid intake. 36 A difference in dietary habits may lead to disparate levels of IGF-I receptor expression, resulting in different effects arising from the same blood IGF-I level.…”
Section: Table IV -Odds Ratio (Or) and 95% Confidence Interval (Ci) Omentioning
confidence: 99%
“…A high-fat diet is associated with aggressive prostate cancer and n-6 fatty acids, including linoleic acid (LA), enhance breast cancer invasion and metastasis (4). LA in combination with azoxymethane results in the upregulation of insulin-like growth factor-I/II receptors (5), Ras (6), cyclooxygenase-2 (7) and high mobility group box-1 (8), which act to accelerate colon carcinogenesis (6,7,9,10). Prolonged treatment with LA induces a quiescent state in CRC cells and the dormancy of subcutaneous tumors in mice, which is thought to be associated with low proliferation of cancer stem cells (CSCs) (11,12).…”
Section: Introductionmentioning
confidence: 99%